ANALISIS NILAI-NILAI FALSAFAH JAWA DALAM BUKU PITUTUR LUHUR BUDAYA JAWA KARYA GUNAWAN SUMODININGRAT SEBAGAI SUMBER BELAJAR PADA PEMBELAJARAN IPS - Arif Widodo; Sa’dun Akbar; Sujito Sujito (Jurnal Penelitian dan Pendidikan IPS, 2017)
This study originated from unrest author of the erosion of understanding the values of local wisdom of the students due to the distortion values of Javanese philosophy which has implications on the deterioration of character of the nation, therefore replanting Values of Javanese Philosophy in learning is especially important in learning IPS. Prior to actualize these values first educators should get a correct understanding of the meaning contained in the philosophy of Java. Therefore in this study the researchers conducted the interpretation of the book "Pitutur Luhur Budaya Jawa" by using heuristic and hermeneutic analysis model so that can know the meaning contained in it properly. This study aimed to explore the content of the values in the Javanese philosophy, character education and its relevance to search for what values are worth to be rebuild in social studies learning. Based on these results it can be seen that there are many good values contained in the book "Pitutur Luhur Budaya Jawa" is still relevant and in line with the eighteen values of character education that disseminated by the government, because they both contain the teaching of manners include honesty, trustworthy, discipline, courtesy, neatness, sincerity, wisdom, self-control, courage, friendship, loyalty, honor and justice. Those values are reflected in hamemayu hayuning bawana, sepi ing pamrih rame ing gawe, alon-alon waton kelakon, mangan ora mangan waton ngumpul, Aja ketungkul marang kalungguhan kadonyan lan kemareman, aja sira deksura, and Aja waton ngomong ning ngomonga nganggo waton.There are some decent character value actualized in social studies lesson although not on the list of eighteen value character because these values are universal can apply to anybody and anywhere. Those values include the patient, neriman, rila, alert, selfless, conscious process and ensure harmony. Actualization of these values can be an answer to the problems that hit the nation's character because of these values is a bridge for people in ngudi kawicaksanan lan ngudi kasampurnaning urip. Keywords: Values of Javanese Philosophy, Pitutur Luhur, learning resources, learning IPS.